PRAGMATIC APPROACH TO PERSONAL SPEECH - RAKHIMOVA UMIDA (International Journal of Innovations in Engineering Research and Technology, 2021)
Today, the social approach to language is becoming more and more interesting, and the audience interested in the essence of the issue is expanding. Indeed, the problems of man and language, the speaker’s consciousness, the linguistic manifestation of the national mentality are widely interpreted. The article discusses some factors affecting human speech, and provides examples. At the same time, it is emphasized that human speech reflects the culture and spirituality of the nation.